2019
DOI: 10.1371/journal.pone.0222080
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome divergence during leaf development in two contrasting switchgrass (Panicum virgatum L.) cultivars

Abstract: The genetics and responses to biotic stressors of tetraploid switchgrass (Panicum virgatum L.) lowland cultivar ‘Kanlow’ and upland cultivar Summer are distinct and can be exploited for trait improvement. In general, there is a paucity of data on the basal differences in transcription across tissue developmental times for switchgrass cultivars. Here, the changes in basal and temporal expression of genes related to leaf functions were evaluated for greenhouse grown ‘Kanlow’, and ‘Summer’ plants. Three biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Similar results were obtained in soybean lines infested with soybean aphids [ 86 ]. Collectively, these results suggested that elevated transcription of plant defense mechanisms could basally be higher in Kanlow relative to Summer, consistent with data reported for Kanlow and Summer plants raised under optimal greenhouse conditions [ 87 ]. A group of co-expressed genes comprising M4 were upregulated in YSA-uninfested and infested plants of Kanlow and downregulated in Summer.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were obtained in soybean lines infested with soybean aphids [ 86 ]. Collectively, these results suggested that elevated transcription of plant defense mechanisms could basally be higher in Kanlow relative to Summer, consistent with data reported for Kanlow and Summer plants raised under optimal greenhouse conditions [ 87 ]. A group of co-expressed genes comprising M4 were upregulated in YSA-uninfested and infested plants of Kanlow and downregulated in Summer.…”
Section: Discussionsupporting
confidence: 89%
“…As examples, four of the NAC TFs in M2 encoded ATNAP homologs [AT1G69490; (Guo and Gan, 2006)]. These four switchgrass NAC genes were also upregulated during the onset of leaf senescence in switchgrass (Palmer et al, 2015;Palmer et al, 2019b), indicating that certain senescence-related KEGG pathways such as 'peroxisomes' and 'fatty acid degradation' were induced by aphid herbivory, either due to loss of leaf functions or as a means to reallocate nutrients away from aphid-infested leaves to other sinks. More intriguingly, a grass specific WRKY (Pavir.5NG041300), related to Arabidopsis WRKY51 (AT5G64810), was strongly induced in M2.…”
Section: Discussionmentioning
confidence: 99%
“…DEGs were identified in the valine, leucine, and isoleucine biosynthesis pathways and their induction in response to osmoregulation under heat stress [ 83 ]. Several studies reported the differences between genotypes for differentially expressed transcripts in response to heat stress and other abiotic stresses as well as maintenance of different mechanisms to cope with the stress impacts [ 36 , 44 , 84 , 85 ]. These results suggest that the differential expression levels of genes involved in different biological pathways can help in understanding the variation in response to heat stress in the blueberry species.…”
Section: Resultsmentioning
confidence: 99%